Preventive hygiene protocol of University of Milan for women during pregnancy: A qualitative and quantitative bacterial plaque analysis prospective original study - Cinzia Maspero; Andrea Fama; Lucia Giannini; Guido Galbiati; Salvatore Batia; Marco Farronato (Elsevier, 2020)
Introduction: The aim of this article is to describe the preventive hygiene protocol of University of Milan for women during pregnancy analyzing the bacterial plaque quantitatively and qualitatively. Materials and methods: A sample of 35 pregnant women following a protocol of periodic visits starting from the first month of pregnancy until the childbirth and in follow up controls were analyzed. Several samples (n = 4) of bacterial plaque for quantitative and qualitative analysis were taken, from the lingual surface of the lower first molar, during the first visit (T0), during the first trimester (T1), during the second or third trimester of pregnancy (T2), and one month after childbirth (T3). Results: By performing a quantitative analysis, it was calculated that the average plaque index (Fig. 1) was n = 48.1% (T0), n = 14.7% (T1), n = 18.4% (T2) and n = 18.9% (T3). The plaque index score presents a downward trend, passing from 48.1% (T0) to 18.9% (T3). The number of total cocci (Fig. 2) was n = 205.39 (T0), n = 57.5(T1), n = 74.6 (T2) and n = 75.4(T3). The number of total bacilli (Fig. 3) was n = 62.7 (T0), n = 23.1 (T1), n = 25.3 (T2), n = 27.1(T3). The total values of cocci and bacilli were correlated and the average trend of the various samples was calculated. By performing a qualitative analysis, the value of G+ cocci (Fig. 5) was n = 2.7 (T0), n = 1.4 (T1), n = 1.4 (T2) and n = 1.5 (T3). The value of G− cocci (Fig. 5) was n = 2.3 (T0), n = 0.7 (T1), n = 1.1 (T2) and n = 1.1 (T3). The value of G+ bacilli (Fig. 6) was n = 1.6 (T0), n = 0.9 (T1), n = 1.2 (T2) and n = 1.2 (T3). The value of G− bacilli (Fig. 6) was n = 1.3 (T0), n = 0.3 (T1), n = 0.7 (T2) and n = 0.7 (T3). Conclusions: The preventive hygiene protocol used in the Dental Hygiene Department of the University of Milan, during the gestation period, is a suitable method for the control of the bacterial plaque. A considerably decrease of the plaque index and bacterial components between the first visit and the subsequent check-ups was calculated. Keywords: Oral health in pregnant, Bacterial plaque, Blood and plaque index